Зміни білковомолочності корів під впливом негативних факторів біогеохімічної провінції - Ємець, З.В.; Маменко, О.М.; Хруцький, С.С. (Фактори експериментальної еволюції організмів, 2013)
Aims. In the article the results of scientific and business experience, which was held in the zone of heavy metals contamination of the biogeochemical province in the negative anthropogenic impact on genetically predetermined quality indicator of protein in the milk of cows. Given production processing method for the production of environmentally safe milk and increasing percentage of protein in the milk of cows with the help of toxic action of mineral additives and biologically active preparation «AVGOR-5». Methods. Laboratory of physico-chemical tests of an experimental material with use of the method of atomic-absorption spectrophotometry ААS-30 (Carl Zeiss, Jena), held – biometric processing of the received results. Results. It should be noted that due to the application of special fodder additives and biologically active preparation was achieved not only the persistence of high levels of protein content in the milk, but also a decrease in urinary excretion of extremely toxic creatinine, which is important for prevention of environmental pollution. Conclusions. Genetically predetermined rate the protein percentage milk may change under the influence of such «shock» factor, as the high content of heavy metals in the feed. A balanced vitamin-mineral additives, used in the feeding of the cows with the product «AVGOR-5», contributed to the normalization of such genetic indicator, as the content of protein in the milk of cows, which in connection with the anthropogenic pollution is significantly decline in province of the Central Donbass with the negative anthropogenic influence that has affected the quality of the products obtained, and may be evidence of the oppression of genetically caused by the capacity of animals in the protein percentage.